Comprehensive comparison between geriatric and nongeriatric patients with trauma. Issue 7 (18th February 2022) - Lin, Pei-Chen; Wu, Nan-Chun; Su, Hsiu-Chen; Hsu, Chien-Chin; Chen, Kuo-Tai
Abstract : Abstract: The incidence of geriatric trauma is increasing due to the growing elderly population. Healthcare providers require a global perspective to differentiate critical factors that might alter patients' prognosis. We retrospectively reviewed all adult patients admitted to a trauma center during a 4-year period. We identified 655 adult trauma patients aged from 18 to 64 (nongeriatric group) and 273 trauma patients ≥65 years (geriatric group). Clinical data were collected and compared between the 2 groups. The geriatric group had a higher incidence of trauma and higher Injury Severity Scores than did the nongeriatric group. Fewer geriatric patients underwent surgical treatment (all patients: geriatric vs nongeriatric: 65.9% vs 70.7%; patients with severe trauma: geriatric vs nongeriatric: 27.6% vs 44.5%). Regarding prognosis, the geriatric group exhibited higher mortality rate and less need for long-term care (geriatric vs nongeriatric: mortality: 5.5% vs 1.8%; long-term care: 2.2% vs 5.0%). We observed that geriatric patients had higher trauma incidence and higher trauma mortality rate. Aging is a definite predictor of poor outcomes for trauma patients. Limited physiological reserves and preference for less aggressive treatment might be the main reasons for poor outcomes in elderly individuals.